Avaliação de diferentes substratos no tratamento de esgoto sanitário por zona de raízes - Pitaluga, Douglas Pereira da Silva (2011)
The present study had the goal of assessing the efficiency and behavior of three substrates in the treatment of sanitary sewage in a root zone system. Specifically the objectives were to assess the behavior of the washed sand, gravel # 0 and gravel # 1 substrates and relate their efficacies in a root zone system with sub-superficial horizontal flow preceded by a septic tank and an anaerobic filter in the treatment of a sewage coming from one university unit. The repetitions of raw sewage constituted of five simple samples and five composed samples. The repetitions of the effluent of each stage of the treatment constituted of nineteen simple samples. All the samples were performed fortnightly and submitted to laboratorial analysis. Were assessed parameters the BOD, DO, COD, thermotolerant coliforms, pH, total phosphorus, Kjeldahl total nitrogen, ammoniacal nitrogen, oil and grease, total solids, total fixed solids and suspended solids. The experimental system of sewage treatment was set up at the Civil Engineering College, located at Campus I of the Federal University of Goiás, in the east region of the city of Goiânia – Goiás, Brazil, which constituted of a septic tank and an anaerobic filter, followed by three independent units of root zones. Each unit of the root zones received the flow of 180 L d-1, which corresponds to the area of a treatment station of 3 m2 per inhabitant. The treatment in these units occurred simultaneously. After thirty days from the beginning of the sewage application in the root zones, the collection of the samples to the analysis of the effluent and affluent quality were started. Considering the plant evapotranspiration, the results were analyzed by the tool Statistical Analysis System – SAS, performing F tests and Tukey – Kramer test with a 5% probability. The percentage efficacies of the three substrates used were similar. There hasn’t been any significant difference between the efficacies of the treatments in the removal of the attributes: COD, Kjeldahl total nitrogen, ammoniacal nitrogen, oil and grease. The treatment with washed sand substrate was more efficient in the removal of BOD and total phosphorous. The gravel # 0 was more efficient in the removal of thermotolerant coliforms, total solids and fixed total solids, and gravel # 1 was more efficient in the removal of suspended solids. After 18 months the system started working, the channel filled with washed sand colmatated.